2016
DOI: 10.1155/2016/1024709
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Methods for Staging in Lung Cancer: Systematic Review and Meta-Analysis

Abstract: Introduction. Endobronchial ultrasound (EBUS) is a procedure that provides access to the mediastinal staging; however, EBUS cannot be used to stage all of the nodes in the mediastinum. In these cases, endoscopic ultrasound (EUS) is used for complete staging. Objective. To provide a synthesis of the evidence on the diagnostic performance of EBUS + EUS in patients undergoing mediastinal staging. Methods. Systematic review and meta-analysis to evaluate the diagnostic yield of EBUS + EUS compared with surgical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
0
19
0
2
Order By: Relevance
“…High negative predictive values often necessitate confirmatory testing 4, 6, 8 . Emerging data support the complementary roles of EUS-NA, EBUS-NA, and mediastinoscopy to avoid futile surgery 4, 8, 14 . In conclusion, there is high level evidence to support PET-CT, endosonography, and the combination of histological and cytological pathology for quality oncologic staging of the mediastinum 4, 6 .…”
Section: Oncologic Quality Indicators In Surgically Resectable Nonmentioning
confidence: 92%
“…High negative predictive values often necessitate confirmatory testing 4, 6, 8 . Emerging data support the complementary roles of EUS-NA, EBUS-NA, and mediastinoscopy to avoid futile surgery 4, 8, 14 . In conclusion, there is high level evidence to support PET-CT, endosonography, and the combination of histological and cytological pathology for quality oncologic staging of the mediastinum 4, 6 .…”
Section: Oncologic Quality Indicators In Surgically Resectable Nonmentioning
confidence: 92%
“…57 Another meta-analysis examined 12 studies (1,515 subjects) to provide a synthesis of the evidence on the diagnostic performance of EBUS plus endoscopic ultrasound in patients who underwent mediastinal staging. 58 The pooled sensitivity for combined EBUS-endoscopic ultra- sound was 87%, and the specificity was 99%, and, for EBUS and endoscopic ultrasound performed with a single bronchoscope group, the sensitivity improved to 88% and specificity improved to 100%. 58 The investigators concluded that EBUS plus endoscopic ultrasound is a highly accurate and safe procedure that should be considered in selected patients with lymphadenopathy that is not accessible with conventional EBUS (Fig.…”
Section: Ebus-tbna and Endoscopic Ultrasound With Bronchoscope-fine Nmentioning
confidence: 92%
“…2). 58 The sensitivity of endoscopic ultrasound-fine needle aspiration and EBUS-TBNA for the detection of metastatic invasion in subjects selected on the basis of CT enlargement or PET positivity (inclusion criteria shared by the above-mentioned studies) was significantly higher than in subjects with negative CT findings or without any selection based on CT or PET. 42,44 The combined use of endoscopic ultrasound and EBUS prevents Ͼ50% of scheduled surgical staging procedures by diagnosing advanced disease in patients with suspected lung cancer and enlarged or PET-positive lymph nodes.…”
Section: Ebus-tbna and Endoscopic Ultrasound With Bronchoscope-fine Nmentioning
confidence: 95%
“…La fibrobroncoscopia flexible es un estudio invasivo que permite la visualización de la vía aérea y la toma de muestras de tejido por medio de lavado broncoalveolar, cepillado bronquial o biopsia transbronquial. 5,[7][8][9][10][11][12] En la actualidad se están desarrollando métodos innovadores fibrobroncoscópicos para la detección temprana de cáncer de pulmón.…”
Section: Wwwmedigraphicorgmxunclassified